Two Cases of Miliary and Disseminated Coccidioidomycosis Following Glucocorticoid Therapy and Literature Review. (February 2022) - Sous, Rowis; Levkiavska, Yuliya; Sharma, Rupam; Jariwal, Roopam; Amodio, Daniela; Johnson, Royce H.; Heidari, Arash; Kuran, Rasha
A 49-year-old man with no significant past medical history received dexamethasone as part of his treatment for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. Less than 3 weeks later, the patient developed acute respiratory distress syndrome. Radiological and serological testing led to a diagnosis of acute hypoxic miliary coccidioidomycosis. A 52-year-old man with a past medical history of chronic kidney disease (CKD) was treated with prednisone for focal segmental glomerulosclerosis (FSGS). Within 2 weeks, this patient developed bilateral lower extremity weakness. Radiology, serology, and lumbar puncture proved a diagnosis of reactivated coccidioidomycosis with miliary pattern and coccidioidomycosis meningoencephalitis with arachnoiditis. Whether treatment with glucocorticoids caused reactivation of coccidioidomycosis is discussed in this case series.